2018
DOI: 10.1007/s11365-018-0495-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brand-related and market signals on franchisees’ entrepreneurial decisions: a multi-country panel data analysis

Abstract: This paper analyses the influence of market and brand-related signals on franchisees' decisions when choosing a franchise brand with which to open an outlet for the first time. Panel data methodology was used to analyse a sample of 1277 chains operating in Spain, Mexico and Peru between 2004 and 2013. The results show that market signals prevail over brand-related signals. Within brand-related signals, franchisees first seek information relating to the brand's sector and then seek information relating to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…They use theoretical and empirical modeling to examine the effectiveness of the franchisor’s ownership structures and contractual terms to signal profitability. Other research suggests that franchisees value the franchisor’s brand name, franchisee performance and strong franchisee protection regulations (Calderón-Monge and Huerta-Zavala, 2014; Calderón-Monge et al , 2019). Lucia-palacios et al (2014) demonstrate how certain factors, such as contractual restrictions, signal positive information about the franchisor.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…They use theoretical and empirical modeling to examine the effectiveness of the franchisor’s ownership structures and contractual terms to signal profitability. Other research suggests that franchisees value the franchisor’s brand name, franchisee performance and strong franchisee protection regulations (Calderón-Monge and Huerta-Zavala, 2014; Calderón-Monge et al , 2019). Lucia-palacios et al (2014) demonstrate how certain factors, such as contractual restrictions, signal positive information about the franchisor.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Others highlight signals that franchisees value, i.e. brand value and franchise performance (Calderón-Monge and Huerta-Zavala, 2014), and strong franchisee protection laws (Calderón-Monge et al , 2019). Further, most signaling research has focused on only one party, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Franchising contributes meaningfully to the performance of the economy. In the past few decades, franchising has turned into one of the most popular business practices in many countries (Croonen and Brand, 2015; Song et al , 2019) as it can contribute to economic development (Calderon-Monge et al , 2019; Rodriguez-Gutierrez et al , 2015). A report by the International Franchise Association (2021) revealed that franchising has a compelling relationship with the economy, particularly the USA, which is one of the leading countries that has a developed and well-structured franchise system.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, franchising has turned into one of the most popular business practices in many countries (Croonen and Brand 2015;Song 2019) as it can contribute to economic development (Calderón-Monge, Huerta-Zavala, and Ayup-González 2019;Rodríguez-Gutiérrez, Moreno, and Tejada 2015). Despite experiencing a high level of success and significant growth rates (Hsu and Jang 2009), there is now a critical mass of academic literature to demonstrate that failure rates in franchising are in fact very high (Stanworth et al 2004).…”
Section: Introductionmentioning
confidence: 99%